Polyolefin microporous membrane

KR1020260137540APending Publication Date: 2026-09-17TORAY BATTERY SEPARATOR FILM KOREA LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250030447
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2026-09-17

Smart Images

  • Figure PAT00001
    Figure PAT00001
  • Figure PAT00002
    Figure PAT00002
Patent Text Reader

Abstract

The present invention relates to a polyolefin microporous membrane for a secondary battery separator having excellent compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyolefin microporous membrane, more specifically, to a polyolefin microporous membrane for a secondary battery separator having excellent compression resistance. Background Technology

[0002] Polyolefin-based microporous membranes are widely used as separator materials for batteries. In particular, when used as separators for lithium-ion secondary batteries, the performance of the porous membrane is closely related to the characteristics, productivity, and safety of the battery. Polyolefin microporous membranes require appropriate permeability, mechanical properties, heat resistance, dimensional stability, shutdown characteristics, and meltdown characteristics. To improve the properties required for these microporous membranes, research and development to increase heat resistance through organic or organic / inorganic coatings is actively underway.

[0003] Recently, as high safety, high power output, and high capacity are required for secondary batteries, separators are also being required to be thinner, stronger, and have higher porosity. However, conventional separators suffer from reduced compressibility as porosity increases; consequently, pressure applied during the battery assembly stage causes a decrease in porosity, leading to a deterioration in physical properties such as battery power output.

[0004] Accordingly, there is a need to develop polyolefin microporous membranes for secondary battery separators with excellent compression resistance. The problem to be solved

[0005] The present invention has the technical objective of providing a polyolefin microporous membrane for secondary battery separators with excellent compression resistance. means of solving the problem

[0006] The present invention provides a polyolefin microporous membrane having a porosity of 40% or more after applying pressure of 7.8 MPa at 70°C for 1 second.

[0007] In addition, the present invention provides a secondary battery comprising the aforementioned polyolefin microporous membrane. Effects of the invention

[0008] The present invention provides a polyolefin microporous membrane for secondary battery separators having excellent compression resistance. A secondary battery separator manufactured using the polyolefin microporous membrane according to the present invention exhibits excellent compression resistance, so that changes in porosity are minimized even when pressure is applied during the battery assembly stage. Therefore, a secondary battery manufactured using the polyolefin microporous membrane of the present invention has excellent physical properties, such as output performance. Specific details for implementing the invention

[0009] The present invention will be described in detail below. However, it is not limited to the following description, and each component may be modified in various ways or selectively combined as needed. Accordingly, it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0011] Polyolefin Microporous Membrane

[0012] The polyolefin microporous membrane of the present invention has a porosity of 40% or more after applying pressure of 7.8 MPa at 70°C for 1 second.

[0013] The present invention can secure excellent compression resistance by controlling the porosity of a polyolefin microporous membrane to a specific range after pressurization. The polyolefin microporous membrane of the present invention may have a porosity of 40% or more, for example, 40 to 50%, after applying pressure of 7.8 MPa at 70°C for 1 second. If the porosity after pressurization is below the aforementioned range, the compression resistance is insufficient, and the output characteristics of the battery may be degraded when applied to a battery; if it exceeds the aforementioned range, stability may be reduced, and internal short circuits may occur.

[0014] The porosity can be calculated using the following formula.

[0015] Porosity (%) = [(w2 - w1) / w2] × 100

[0016] In the above formula,

[0017] w1 is the mass of the polyolefin microporous membrane

[0018] w2 is the mass of a non-porous membrane of the same size made of a polyolefin composition

[0019] For example, the above polyolefin microporous membrane may have a change in porosity of 15% or less, for example, 10% or less, after applying pressure at a force of 7.8 MPa at 70°C for 1 second, based on the porosity before applying pressure. If the change in porosity after pressure exceeds the aforementioned range, the compressibility is insufficient, and when applied to a battery, the output characteristics of the battery may be degraded.

[0020] For example, the above polyolefin microporous membrane may have a light transmittance / unit mass of 12% / g / m² or more, for example, 12 to 25% / g / m², after applying pressure of 7.8 MPa at 70°C for 1 second. The higher the light transmittance of the microporous membrane, the smaller the pore size becomes, the lower the tortuouslyity becomes, and the shorter the path of ion movement becomes, which lowers the battery resistance and, accordingly, can improve the charge / discharge efficiency and output characteristics of the battery. If the light transmittance / unit mass after pressure application is below the aforementioned range, the pore size and tortuously increase, and as the battery resistance increases, the output characteristics of the battery may deteriorate; if it exceeds the aforementioned range, the battery life and safety may be reduced.

[0021] Light transmittance can be measured using a spectrophotometer, for example, the V-750 Spectrophotometer (JAS, Japan, 800 nm wavelength).

[0022] For example, the above polyolefin microporous membrane may have an air permeability of 80 seconds or less, for example, 60 to 80 seconds, after applying pressure of 7.8 MPa at 70°C for 1 second. If the air permeability after pressure is below the aforementioned range, the battery life and safety may be reduced, and if it exceeds the aforementioned range, the output characteristics of the battery may be reduced.

[0023] Air permeability can be measured according to JISP8117 using an Oken-type air resistance meter, for example, the EGO-1T (Asahi Seiko Co. Ltd.).

[0024] For example, the above polyolefin microporous membrane may have a membrane thickness of 2 to 20 μm, for example, 3 to 8 μm, after applying pressure of 7.8 MPa at 70°C for 1 second. If the membrane thickness after pressure is less than the aforementioned range, safety may be reduced and internal short circuits may occur, and if it exceeds the aforementioned range, the battery capacity may be reduced or output characteristics may be degraded.

[0025] The microporous membrane of the present invention is formed from a polyolefin resin, and any polyolefin resin used in the relevant technical field may be used without special limitations. For example, the polyolefin resin may include polyethylene resin, polypropylene resin, or a mixture thereof. As an example, the polyolefin resin may be polyethylene resin.

[0026] For example, the weight-average molecular weight of the polyolefin resin may be between 800,000 and 3 million, for example, between 1 million and 2 million. When using a polyolefin resin within the aforementioned molecular weight range, excellent compression resistance can be secured. If the weight-average molecular weight of the polyolefin resin is below the aforementioned range, mechanical strength may decrease, and if it exceeds the aforementioned range, kneading ability may decrease.

[0027] For example, the maximum peak top melting point on the melting curve obtained during the second heating step by differential scanning calorimetry (DSC) of the polyolefin resin may be 130 to 140 °C, for example, 133 to 137 °C. By controlling the maximum peak top melting point on the melting curve obtained during the second heating step by DSC to the aforementioned range, a polyolefin microporous membrane with excellent uniformity and compression resistance can be obtained. If the maximum peak top melting point on the melting curve obtained during the second heating step by DSC is below the aforementioned range, mechanical strength and compression resistance may decrease, and if it exceeds the aforementioned range, kneading ability may decrease.

[0028] For example, the half-width of the heat flow obtained during the second heating step by DSC of the above polyolefin resin may be 10°C or less, for example, 3 to 9.5°C. By controlling the half-width of the heat flow obtained during the second heating step by DSC to the aforementioned range, a polyolefin microporous membrane with excellent uniformity and compression resistance can be obtained. If the half-width of the heat flow obtained during the second heating step by DSC is less than the aforementioned range, processability may be reduced, and if it exceeds the aforementioned range, physical properties may become non-uniform.

[0029] For example, based on the total weight of the polyolefin resin, it may contain at least 50% by weight of polyethylene resin, for example, at least 60% by weight. High-density polyethylene (HDPE), medium-density polyethylene (MDPE), or low-density polyethylene (LDPE) may be used as the polyethylene without limitation. The polyethylene may include two or more types of polyethylene with different weight-average molecular weights or densities.

[0030] For example, based on the total weight of the polyolefin resin, it may contain 50% by weight or less of polypropylene resin, for example, 40% by weight. High-density polypropylene (HDPP), medium-density polypropylene (MDPP), or low-density polypropylene (LDPP), etc., may be used as the polypropylene without limitation. The polypropylene may include two or more types of polypropylene with different weight-average molecular weights or densities.

[0031] To improve the characteristics as a battery separator, the polyolefin resin may further include a polyolefin that provides a shutdown function. As the polyolefin that provides the shutdown function, low-density polyethylene (LDPE) or polyethylene wax may be used. As for the low-density polyethylene (LDPE), at least one selected from the group consisting of branched LDPE, linear LDPE, and ethylene / α-olefin copolymer produced by a single-site catalyst may be used, and the amount added thereof can be appropriately controlled within a range known in the relevant art.

[0032] If necessary, conventional additives known in the relevant technical field, such as antioxidants, pore-forming agents, etc., may be included to the extent that they do not impair the effects of the present invention.

[0034] Method for manufacturing a polyolefin microporous membrane

[0035] The method for manufacturing the polyolefin microporous membrane of the present invention is not particularly limited. For example, the method for manufacturing the polyolefin microporous membrane of the present invention may comprise: (1) a step of preparing a polyolefin solution by melt-kneading a polyolefin and a plasticizer; (2) a step of forming a sheet-shaped body by extruding the polyolefin solution and then cooling it; (3) a first stretching step of forming a film by stretching the sheet-shaped body; (4) a step of removing the plasticizer from the film; (5) a step of drying the film from which the plasticizer has been removed; (6) a second stretching step of re-stretching the dried film; and (7) a heat treatment step.

[0037] (1) Manufacturing process of polyolefin solution

[0038] A polyolefin solution is prepared by melt-kneading a polyolefin resin and a plasticizer. The melt-kneading of a composition containing a polyolefin resin and a plasticizer can be carried out according to conventional methods known in the art. For example, a method can be used in which the polyolefin resin and the plasticizer are melt-kneaded at a temperature of 100 to 250 °C and a twin-screw extruder is used.

[0039] The content of the polyolefin resin is not particularly limited and may be included in an amount of 15 to 50 weight%, for example, 20 to 40 weight%, based on the total weight of the composition including the polyolefin resin and the plasticizer.

[0040] As a plasticizer, any plasticizer component known in the art may be used without special limitations; for example, any organic compound that forms a single phase with the polyolefin resin at the extrusion temperature may be used. Non-limiting examples of usable plasticizers include aliphatic or cyclic hydrocarbons such as nonan, decane, decalin, liquid paraffin (or paraffin oil) such as Liquid Paraffin (LP), and paraffin wax; phthalic acid esters such as dibutyl phthalate and dioctyl phthalate; fatty acids having 10 to 20 carbon atoms such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid; There are fatty acid alcohols having 10 to 20 carbon atoms, such as palmitic acid alcohol, stearic acid alcohol, and oleic acid alcohol, or mixtures of two or more of these.

[0041] The content of the above plasticizer is not particularly limited and may be included in an amount of 50 to 90 weight%, for example 60 to 85 weight%, based on the total weight of the composition comprising the polyolefin resin and the plasticizer.

[0042] In addition to the aforementioned polyolefin-based resin, other resins, inorganic particles, additives, etc. used in the relevant technical field may be included.

[0044] (2) Formation process of sheet-shaped product

[0045] The polyolefin solution prepared in step (1) above is extruded through a die equipped with an extruder and cooled to form a sheet-shaped product. The cooling method is not particularly limited, and methods known in the art, such as cooling by contacting a cooling roll, cooling with cold air, or cooling by impregnating with cold water, may be used.

[0047] (3) First stretching process

[0048] The sheet shape obtained in step (2) above is biaxially stretched one or more times to form a film.

[0049] In the present invention, the first stretching process may be performed at a predetermined ratio according to conventional methods in the art, such as the tenter method, roll method, inflation method, rolling method, or a combination of these methods. In the case of biaxial stretching, either simultaneous stretching or sequential stretching may be performed.

[0050] In the above first stretching process, the stretching ratio varies depending on the thickness of the sheet-shaped workpiece, but in biaxial stretching, it is appropriate to perform at least 2x2 in either direction, and for example, it can be performed in the range of 3 to 10 times.

[0051] During the first stretching process, the strength of the microporous membrane can be controlled by adjusting the stretching speed and temperature. For example, high-speed, low-temperature stretching can be performed, and in this case, a high-strength microporous membrane can be provided.

[0052] In the first stretching process above, the stretching temperature / stretching speed ratio may be 2.5 to 3.5 ℃ / mpm, for example, 2.8 to 3.2 ℃ / mpm. Under conditions within this range, a high-strength microporous membrane can be manufactured by high-speed, low-temperature stretching within a range where fracture does not occur. In the first stretching, if the stretching temperature / stretching speed ratio is below the aforementioned range, mechanical strength and coating properties may be reduced, and if it exceeds the aforementioned range, productivity may be reduced due to fracture.

[0054] (4) Plasticizer removal process

[0055] The plasticizer is extracted from the stretched film using a cleaning solvent. Since the polyolefin phase is phase-separated from the plasticizer, removing the plasticizer yields a porous membrane with a plurality of pore structures. Conventional methods known in the art may be used to remove the plasticizer without any particular limitations.

[0056] As the above-mentioned cleaning solvent, any organic solvent capable of extracting the plasticizer may be used without special restrictions. For example, halogenated hydrocarbons such as methylene chloride, 1,1,1-trichloroethane, and fluorocarbons, which have high extraction efficiency and are easy to dry; hydrocarbons such as n-hexane and cyclohexane; alcohols such as ethanol and isopropanol; and ketones such as acetone and 2-butanone may be used. For example, when liquid paraffin is used as a plasticizer, methylene chloride may be used as the cleaning solvent. Since most of the above-mentioned cleaning solvents are highly volatile and toxic, water may be used to suppress the volatilization of the organic solvent if necessary.

[0058] (5) Drying process

[0059] The polyolefin microporous membrane obtained by plasticizer removal can be dried using conventional drying methods known in the art. For example, heating drying and air drying methods may be used.

[0061] (6) Second stretching process

[0062] The dried film is re-stretched again in at least one uniaxial direction. The second stretching process is performed while heating the film, and the same stretching method as the first stretching process may be used. The stretching may be uniaxial stretching or biaxial stretching.

[0063] During the second stretching process, the strength of the microporous membrane can be controlled by adjusting the stretching speed and temperature. For example, high-speed, low-temperature stretching can be performed, and in this case, a high-strength microporous membrane can be provided.

[0064] In the second stretching process above, the stretching temperature / stretching speed ratio may be 1.0 to 1.6 ℃ / mpm, for example, 1.1 to 1.5 ℃ / mpm. Under conditions of the above range, a high-strength microporous membrane can be manufactured by dry stretching within a range that does not break. In the second stretching, if the stretching temperature / stretching speed ratio is below the aforementioned range, productivity may be reduced due to breakage, and if it exceeds the aforementioned range, mechanical strength may be reduced.

[0065] The magnification ratio in the uniaxial direction of the second stretching may be 1.0 to 2.0 times, for example, 1.2 to 1.8 times. For example, in the case of uniaxial stretching, it may be 1.0 to 1.8 times in the MD direction or TD direction, and in the case of biaxial stretching, it may be 1.0 to 1.8 times in the MD direction and TD direction, respectively. In the case of biaxial stretching, the stretching magnification ratios in the MD direction and TD direction may be the same or different. By adjusting the stretching magnification ratio to the aforementioned range, a decrease in permeability, electrolyte absorption, and compressibility can be prevented, and the fibril may not become excessively thin and a decrease in heat shrinkage resistance can be prevented.

[0067] (7) Heat treatment process

[0068] The above-mentioned re-stretched film is fixed and heat-treated to obtain a microporous membrane. The heat treatment method may be any conventional method known in the art without special limitations, and, for example, heat-setting treatment and / or heat-relaxation treatment may be performed.

[0069] For example, a heat-setting treatment can be performed. In this case, the network structure consisting of fibrils formed by the second stretching process is maintained and the crystals of the porous membrane are stabilized, so that a microporous membrane with appropriately controlled micropore diameter and excellent strength can be produced.

[0070] The above heat-setting treatment can be performed within a temperature range above the crystal dispersion temperature and below the melting point of the polyolefin resin constituting the microporous membrane. The above heat-setting treatment can be performed by a tenter method, a roll method, a rolling method, etc.

[0071] The above thermal relaxation treatment may be performed using a tenter method, a roll method, a compression method, etc., or may be performed using a belt conveyor or a floating roll. The thermal relaxation treatment may be performed in at least one direction at a relaxation rate of 20% or less, for example, 10% or less.

[0073] Secondary Battery

[0074] The present invention provides a secondary battery comprising the aforementioned polyolefin microporous membrane, for example, a lithium-ion secondary battery.

[0075] The secondary battery of the present invention may be manufactured according to conventional methods known in the art, except for using a separator made of a polyolefin microporous membrane according to the present invention. For example, it may be manufactured by interposing a separator between a positive electrode and a negative electrode and introducing a non-aqueous electrolyte. Herein, regarding the components of the positive electrode, negative electrode, electrolyte, and other additives if necessary, excluding the aforementioned separator, they conform to the components of conventional secondary batteries known in the art.

[0076] For example, the above-mentioned cathode may be manufactured using a conventional cathode active material for secondary batteries known in the art, and non-limiting examples thereof include lithium transition metal complex oxides such as LiMxOy (M = Co, Ni, Mn, CoaNibMnc) (e.g., lithium manganese complex oxides such as LiMn2O4, lithium nickel oxides such as LiNiO2, lithium cobalt oxides such as LiCoO2, and those in which some of the manganese, nickel, or cobalt in these oxides are substituted with other conventional transition metals or aluminum, or vanadium oxide containing lithium, etc.) or chalcogen compounds (e.g., manganese dioxide, titanium disulfide, molybdenum disulfide, etc.).

[0077] For example, the above-mentioned cathode can be manufactured using a conventional cathode active material for secondary batteries known in the art, and non-limiting examples thereof include materials capable of intercalating / deintercalating lithium ions, such as lithium metal or lithium alloy, coke, artificial graphite, natural graphite, combustion products of organic polymer compounds, carbon fibers, silicon-based materials, tin-based materials, etc.

[0078] Non-aqueous electrolytes include electrolyte components commonly known in the relevant technical field, such as electrolyte salts and electrolyte solvents.

[0079] The above electrolyte salt may be composed of a combination of (i) a cation selected from the group consisting of Li+, Na+, and K+ and (ii) anion selected from the group consisting of PF6-, BF4-, Cl-, Br-, I-, ClO4-, AsF6-, CH3CO2-, CF3SO3-, N(CF3SO2)2-, and C(CF2SO2)3-, among which a lithium salt is preferred. Specific examples of lithium salts include LiClO4, LiCF3SO3, LiPF6, LiBF4, LiAsF6, and LiN(CF3SO2)2. These electrolyte salts may be used alone or in a mixture of two or more types.

[0080] Cyclic carbonates, linear carbonates, lactones, ethers, esters, acetonitrile, lactams, and ketones may be used as the above electrolyte solvents.

[0081] Examples of the above-mentioned cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), etc. Examples of the above-mentioned linear carbonates include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), etc. Examples of the above-mentioned lactone include gamma-butyrolactone (GBL), and examples of the above-mentioned ethers include dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. Examples of the above esters include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl pivalate, etc. Additionally, the above lactam includes N-methyl-2-pyrrolidone (NMP), etc., and the above ketone includes polymethylvinyl ketone. Furthermore, halogen derivatives of the above organic solvent may be used, but are not limited thereto. In addition, glyme, deglyme, triglyme, and tetraglyme may be used as the above organic solvent. These organic solvents may be used alone or in a mixture of two or more types.

[0083] The present invention will be explained in more detail below through examples. However, the following examples are intended only to aid in understanding the present invention and do not imply that the scope of the present invention is limited to these examples in any way.

[0085] [Examples 1-5: Preparation of Microporous Membranes]

[0086] According to Table 1 below, a microporous membrane of each example was prepared. The porosity of the microporous membrane according to each example was measured before and after compression (pressurization at 70°C with a force of 7.8 MPa for 1 second) using the following method, and the results are shown in Table 1 below.

[0088] [Comparative Example 1-5: Preparation of Microporous Membrane]

[0089] According to Table 1 below, microporous membranes of each comparative example were prepared. The porosity of the microporous membranes according to each comparative example was measured before and after compression (pressurization at 70°C with a force of 7.8 MPa for 1 second) using the following method, and the results are shown in Table 1 below.

[0091] porosity

[0092] The porosity was calculated using the following formula.

[0093] Porosity (%) = [(w2 - w1) / w2] × 100

[0094] w1: Mass of the polyolefin microporous membrane of each example and comparative example

[0095] w2: Mass of a pore-free membrane of the same size made of the polyolefin composition used in each example and comparative example

[0097]

[0099] Resin 1: Polyethylene (Mw 1,700,000 g / mol, resin concentration 19 wt%, DSC 2nd heat flow half-width 9.0 ℃)

[0100] Resin 2: Polyethylene (Mw 1,000,000 g / mol, resin concentration 22 wt%, DSC 2nd heat flow halfway 6.5 ℃)

[0101] Resin 3: Polyethylene (Mw 1,500,000 g / mol, resin concentration 21 wt%, DSC 2nd heat flow half-width 7.0 ℃)

[0102] Resin 4: Polyethylene (Mw 1,500,000 g / mol, resin concentration 20 wt%, DSC 2nd heat flow half-width 9.5 ℃)

[0103] Resin 5: Polyethylene (Mw 2,000,000 g / mol, resin concentration 18 wt%, DSC 2nd heat flow half-width 8.0 ℃)

[0104] Resin 6: Polyethylene (Mw 1,000,000 g / mol, resin concentration 22 wt%, DSC 2nd heat flow half-width 13 ℃)

[0105] Resin 7: Polyethylene (Mw 700,000 g / mol, resin concentration 30 wt%, DSC 2nd heat flow half-width 15 ℃)

[0106] Resin 8: Polyethylene (Mw 1,600,000 g / mol, resin concentration 22 wt%, DSC 2nd heat flow half-width 11 ℃)

[0107] Resin 9: Polyethylene (Mw 1,100,000 g / mol, resin concentration 22 wt%, DSC 2nd heat flow half-width 12 ℃)

[0108] Resin 10: Polyethylene (Mw 1,500,000 g / mol, resin concentration 20 wt%, DSC 2nd heat flow half-width 11 ℃)

[0110] [Physical Property Evaluation]

[0111] The physical properties of the microporous membranes prepared in each example and comparative example were tested as follows, and the results are listed in Table 2 below. Each physical property was measured before and after compression (pressure applied for 1 second with a force of 7.8 MPa at 70 ℃).

[0113] airway

[0114] Measurements were taken according to JISP8117 using an Oken-type air resistance meter (Asahi Seiko Co. Ltd., EGO-1T).

[0116] Penetration strength

[0117] The maximum load was measured when each microporous membrane was pierced at a speed of 2 mm / second with a 1 mm diameter needle having a spherical tip (radius of curvature R: 0.5 mm).

[0119] Light transmittance

[0120] Light transmittance was measured using a V-750 Spectrophotometer (JAS, Japan, 800 nm wavelength).

[0122] Battery output characteristics

[0123] After manufacturing a CR2032 type coin cell using the microporous membrane prepared in each example and comparative example, the impedance was measured using Solartron's 1255B / 1470E. The cell output characteristics were evaluated according to the following criteria by calculating Impedance (Ω) / Porosity (%) * 100.

[0124] O: 5 Ω / % or less

[0125] △: Greater than 5 Ω / %, less than 6.0 Ω / %

[0126] X: 6.0 Ω / % or higher

[0128]

[0130] As shown in Table 2, the microporous membrane of Examples 1-5 according to the present invention and the secondary battery manufactured using it exhibited excellent properties across all measured parameters. On the other hand, the microporous membrane of Comparative Examples 1-5, in which the porosity after compression fell outside the range of the present invention, and the secondary battery manufactured using it exhibited inferior properties across all measured parameters compared to Examples 1-5.

Claims

Claim 1 Polyolefin microporous membrane having a porosity of 40% or more after applying pressure of 7.8 MPa at 70 ℃ for 1 second. Claim 2 A polyolefin microporous membrane according to claim 1, wherein the change in porosity is 15% or less after applying pressure at a force of 7.8 MPa at 70 ℃ for 1 second, based on the porosity before applying pressure. Claim 3 A polyolefin microporous membrane according to claim 1, having a light transmittance / unit mass of 12 % / g / m² or more after applying pressure of 7.8 MPa at 70 ℃ for 1 second. Claim 4 A polyolefin microporous membrane according to claim 1, having an air permeability of 80 seconds or less after applying pressure of 7.8 MPa at 70°C for 1 second. Claim 5 A polyolefin microporous membrane having a thickness of 2 to 20 μm after applying pressure of 7.8 MPa at 70 ℃ for 1 second. Claim 6 In claim 1, a polyolefin microporous membrane having a weight-average molecular weight of a polyolefin resin constituting the polyolefin microporous membrane of 800,000 to 3,000,000. Claim 7 A polyolefin microporous membrane according to claim 1, wherein the maximum peak top melting point on the melting curve obtained during the second heating step by differential scanning calorimetry (DSC) of the polyolefin resin constituting the polyolefin microporous membrane is 130 to 140 ℃. Claim 8 A polyolefin microporous membrane according to claim 1, wherein the half-width of the heat flow obtained during the second heating step by DSC of the polyolefin resin constituting the polyolefin microporous membrane is 10°C or less. Claim 9 A polyolefin microporous membrane manufactured by a manufacturing process comprising, in claim 1, a first stretching process having a stretching temperature / stretching speed ratio of 2.5 to 3.5 ℃ / mpm and a second stretching process having a stretching temperature / stretching speed ratio of 1.0 to 1.6 ℃ / mpm. Claim 10 A secondary battery comprising a polyolefin microporous membrane according to any one of claims 1 to 9.